Kamlet–Taft Solvation Parameters of Solvate Ionic Liquids. Issue 19 (1st September 2016) - Dolan, Dr Andrew; Sherman, Dylan A.; Atkin, Rob; Warr, Gregory G.
Abstract: The Kamlet–Taft solvent parameters of solvate ionic liquids (SILs) prepared from lithium salts with glyme and glycol ligands are determined. The dipolarity/polarisibilities (π*) are high, similar to those found in conventional ionic liquids. The H‐bond basicities ( β ) depend strongly on the anion. The H‐bond acidities ( α ) are high in both glyme and glycol SILs, indicating that the lithium is acting as a H‐bond donor site. "Poor" SILs have glyme‐rich and salt‐rich regions. In these liquids the π* and β values are almost identical to the parent glyme or glycol, and the α values are determined by the salt alone. Abstract : Like an H‐bond : Spectroscopic probing of Kamlet–Taft solvent parameters reveals unusually high H‐bond acidity of a range of lithium solvate ionic liquids. Their H‐bond basicity depends strongly on how the anion modulates the coordination of the cation by the glyme.